A mental intelligence to improve the effectiveness of local contribution to public policies in Italy - Cristiano Trindade de Angelis; Maurício Mota Saboya Pinheiro (Gestão e Desenvolvimento)
The current situation shows the importance of the insertion of society in the relationship between the State and the private sector, with the objective of collaboration to improve government programs. Shared Governance is one of the great challenges that the Italian government is currently facing to avoid the crises of governance (society) and governability (negotiation with opposition and work with the public administration), in particular after the decision of the new government (September 2022) to extinguish the Reform of the Public Administration - National Recovery and Resilience Plan - PNRR, and also the largest social participation initiative in Italy, the Tuscany Regional Policy for Social Participation - TRPP. This article recuperates the good points of PNRR and TRPP and another case study in Emilia-Romagna region. Offering a new perspective to the existing literature, this paper share the “famous” model for the Public Administration, the New Public Service (NPS), created to spread the idea that public service is seen as an extension of citizenship, and therefore both government and citizens need to abandon short-term interests and imitation of the competition of private sector of the New Public Management (NPM), assuming collaborative roles in building an educated and mature civil society. Based in a literature review on the NPS model, Knowledge Management - KM, Governmental Intelligence -OI and Cultural Intelligence -CI, the article presents a theoretical model of CI, OI and Social Participation – SP (CIGISP) to improve the effectiveness of public policies. This work concludes that CIGISP model is useful to identify how the learning by comparison with other values, believes and assumptions (CI) and use of GI Practices leads to a better quality of social participation.